Cannabinoids Regulate Sensory Processing in Early Olfactory and Visual Neural Circuits - Heinbockel, Thomas; Straiker, Alex (Frontiers in Neural Circuits, 2021)
Our sensory systems such as the olfactory and visual system are the target of neuromodulatory regulation. This neuromodulation starts at the level of sensory receptors and extends into cortical processing. A relatively new group of neuromodulators includes cannabinoids. These form a group of chemical substances that are found in the cannabis plant. Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD) are the main cannabinoids. Our body produces chemical substances that act like THC in the brain and nervous system, the endogenous cannabinoids or endocannabinoids, also nicknamed the brain’s own marijuana. While the function of the endocannabinoid system is understood fairly well in limbic structures such as the hippocampus and the amygdala, this signaling system is less well understood in the olfactory pathway and visual system. Here, we describe and compare endocannabinoids as signaling molecules in the olfactory and visual system and the relevance of the endocannabinoid system for synaptic plasticity.